Seroprevalence and factors associated with SARS-CoV-2 infection among healthcare workers: cross-sectional study - Watheq Thabet Taher (17541210) (2023)
Background Healthcare workers (HCWs) are at a higher risk of contracting COVID-19 due to their close contact with infected patients. However, the true burden of COVID-19 among HCWs in Yemen is unknown due to the inadequate availability of healthcare and the subclinical nature of the disease. This study aims to estimate the seroprevalence of SARS-CoV-2 infection among HCWs in two Yemeni governorates and identify associated factors using a cross-sectional design. Method A total of 404 HCWs were surveyed from June 2022 to September 2022 in Lahj and AL-Dhalea hospitals. A self-administered questionnaire collected demographic data, COVID-19 infection history, and vaccination status. A total of 404 human sera were tested using a specific electrochemiluminescence immunoassay assay. Association analysis was conducted to identify associations between antibody prevalence and demographic and vaccine-related variables. Result The median age of the HCWs was 31 (Range 20–64) years, with 65.0% being male and 35.0% female. Of all HCWs, 94% were SARS-CoV-2 seropositive and 77.0% had no confirmed test of COVID-19-related symptoms. There was no significant association between seropositivity and demographic factors such as age, gender, occupation, or COVID-19 vaccination (P > 0.05). Conclusion The seroprevalence of SARS-CoV-2 was high among HCWs in Yemen, primarily due to natural infection rather than vaccination. Compliance with infection prevention and control measures did not significantly affect seropositivity. This study highlights the need for improved healthcare systems and resources to reduce the burden of COVID-19 and promote infection prevention and control (IPC) measures among HCWs in Yemen. Other Information Published in: BMC Infectious Diseases License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12879-023-08760-5